Character, Gender, and Populism: How Female Populist Voters Judge the Character of Political Leaders - Cristine de Clercy; Gerard Seijts; Ana Ruiz Pardo (Politics and Governance)
Many voters choose to follow political leaders based on an assessment of character. However, political scientists employ relatively few tools to precisely measure character, and there is even less study of the key factors that influence such voter assessments. We employ an analytical framework drawn from the management sciences to examine how a sample of voting-age, anglophone Canadians judged the character of Canadian Prime Minister Justin Trudeau during the 2020–2021 Covid-19 pandemic time frame. We propose and find support for the assertion that gender and right-wing populism are important explanatory variables. Importantly, and controlling for a host of demographic variables, the interaction of gender and populism suggests that subscription to right-wing populist attitudes may more significantly corrode character assessments among female voters than among male voters.